COOPERATION BETWEEN THE REPUBLIC OF TAJIKISTAN AND THE INTERNATIONAL MONETARY FUND: RELIMINARY RESULTS - KURBANOV, Sobir (CENTRAL ASIA AND THE CAUCASUS, 2004)
In October 2003, a regular IMF mission visited Dushanbe to review its second Poverty Reduction and Growth Facility (PRGF) Arrangement in the country. If it fulfilled the reform conditions/goals designated under this arrangement, the Tajik Republic could draw an amount in several installments equal to 89 million. The mission held several meetings with the Tajikistan government and representatives from several sponsor states. These meetings resulted in an assessment of the level of economic and structural transformations in the republic. The official chronicles were peppered with brief statements on the achievements, as well as with positive responses by the mission’s experts. But along with the mutual compliments, there were also statements of blatant displeasure on both sides. And what is more, the mass media provided very scant coverage of their viewpoints, the mission’s activity, and the course of the negotiations. The mission worked behind closed doors, which has already become a certain tradition. The press did not publish a single interview with its members, or any statements by government officials, or any of the discussions and talks. The public was presented with only very laconic reports from the information agencies, and the population has very little idea about the authors, areas, course, and strategy of the eco-nomic reforms. Admittedly, in private conversations, government officials and economists are usually quick to assure that there can be no doubt about the IMF’s authority, that it is the so-called “exclusive owner of the author’s rights,” and sets the rules of the game for these reforms. So in order to understand how the socio-economic reforms are developing in the republic and predict their progress, we must first take a look at how cooperation is being established between our country and the IMF. This is particularly important since during the aforementioned negotiations, a whole host of problems was exposed, which cannot longer be kept under wraps. The underlying lack of correlation between the sides’ viewpoints and their barely restrained irritation have come to the surface, which naturally did not feature in the sparse official chronicles.